Photon and Polariton Condensates in Microcavities - Liew, Timothy Chi Hin (2017)
We study thermalisation coherence and spin dynamics of photon and polariton Bose-Einstein condensates (BECs). We observe a Bose Einstein distribution, buildup of long-range order and spontaneous symmetry breaking.